Effects of Onion Residue, Bovine Manure Compost and Compost Tea on Soils and on the Agroecological Production of Onions - Orden, Luciano; Ferreiro, Nicolás; Satti, Patricia; Navas-Gracia, Luis Manuel; Chico-Santamarta, Leticia; Rodríguez, Roberto A. (MDPI, 2022)
Organic solid wastes are rarely considered when planning for rural production in Argentina. Onion production in the low valley of Río Colorado (Buenos Aires) generates between 12,000 and 20,000 Mg year−1 of vegetal wastes (i.e., leaves, stems, skins, roots) from harvesting, cleaning and classification of bulbs, causing many problems with their management. The aim of this work is to study the effect of different doses of onion residue-bovine manure compost and onion residue-bovine manure compost tea on the soil physicochemical properties, microbial activity and agroecological onion production in sandy soil. Results showed that the highest dose of compost caused the highest effects on soil pH, electrical conductivity and nutrient content. Soil enzymatic activities were already high in the soil before the compost was applied, which may have contributed to the small effect caused by any dose on soil activity. A significant positive effect on bulb weight and organic onion yield were found as a result of the amendment and growing season. In conclusion, agroecological production of onion with the addition of a 300 kg N ha−1 compost and compost tea guarantee yields comparable to those of conventional fertilization, as occurred during the two growing seasons of this study.